Unpacking Integrated Result Based Management (IRBM) Concept - Amos Muguti; Tonderai Chiunye; Chipo Mutongi; Precious Kandufa (EPRA Journals, 2023)
The concept of Integrated Result Based Management (IRBM) was first introduced in Malaysia in 1990 and Zimbabwe first adopted it in 2005 under the guidance of the Malaysian government. In Zimbabwe, before the adoption of RBM, accountability was limited to inputs, that is, what was bought and how wisely the money was spent. This type of scenario breeds an "audit" mentality which may have ensured that large volumes of books were put in place but providing little information on whether programmes or projects achieved their intended outcomes and impacts (Government of Zimbabwe, 2004). The RBM systems across the globe have been triggered by the growing concerns and pressure from both internal and external stakeholders for government to provide more tangible results. The article unpacks the concept of IRBM and make use of City of Harare to demonstrate it.